IN-GAME ADVERTISING: ANALYZING THE EFFECTS OF BRAND CONGRUITY, INTEGRATION, AND PROMINENCE TOWARDS IGA ATTITUDE AND PURCHASE INTENTION - Soebandhi, Santirianingrum; Andriansyah, Yuan (Jurnal Manajemen Teknologi, 2017)
Abstract. Currently mobile in-game advertising (IGA) has become a promotional medium that is widely used in introducing and offering products to consumers. Using an existing online racing game, this study analyzed the effect of brand congruity, integration, and prominence on attitudes toward IGA and purchase intention on brands that advertised in this game. A total of 100 respondents ranging from 16 to 35 years old were involved. Partial Least Squares analysis was used as the data technique analysis. The results show that brand congruity, integration, and prominence have a significant effect on consumer attitudes toward IGA. However, those do not have effect on purchase intention.Keywords: Brand congruity, brand integration, brand prominence, attitude towards in-game advertising, purchase intentionAbstrak. Saat ini mobile in-game advertising (IGA) telah menjadi media promosi yang secara luas digunakan dalam mengenalkan dan menawarkan produk kepada konsumen. Dengan menggunakan game balap online yang ada, penelitian ini menganalisis pengaruh kesesuian, integrasi, dan prominen merek pada sikap terhadap IGA dan niat beli pada merek yang diiklankan dalam game ini. Sebanyak 100 responden dengan rentang usia 16 sampai 35 tahun dilibatkan dalam penelitian ini. Analisis Partial Least Squares digunakan sebagai teknik analisis data. Hasil menunjukkan bahwa kesesuian, integrasi, dan prominen merek berpengaruh signifikan terhadap sikap konsumen terhadap IGA. Namun, hal tersebut tidak berpengaruh pada niat beli.Kata kunci: Kesesuaian merek, integrasi merek, prominen merek, sikap terhadap in-game advertising, minat beli